ANALISIS PASAR BARANG DAN PASAR UANG DI INDONESIA : PENDEKATAN KEBIJAKAN FISKAL DAN KEBIJAKAN MONETER - Siska Rahmi; Ali Anis; Dewi Zaini Putri (Universitas Negeri Padang, 2018)
This study aims to analyze the (1) multiplier of fiscal policy and monetary policy, (2) equilibrium market of goods and money market in Indonesia, (3) effective policy to stabilize Indonesian economy by using Ordinary Least Square (OLS) method. The results of the research show that (1) a fiscal multiplier is 0.06 and a monetary multiplier is 1.17, (2) the equilibrium is at the interest rate of 1,81% and the GDP of Rp. 935.235,6 billion, and (3) the effective policy is monetary policy in stabilizing the economy.